Strategic Voting at the Romanian 2008 Local Elections - Albescu, Andrada Maria; Irina, IoniÅ£Äƒ Dana; Mateescu , Silviu Dan (Mediterranean Journal of Social Sciences, 2012)
The aim of this article is to measure the extent to which voters cast their ballots strategically at the Romanian 2008local elections. Our interest was prompted by the introduction of a mixed-member electoral system for local elections. Onecommon characteristic of mixed-member electoral systems is that they present the voter with the opportunity for strategicbehavior. For the purpose of measuring strategic voting we use three methods: 1. we compare the number of votes received bycandidates in the single member district race with the number of votes received by their parties in the proportional representationrace; 2. we calculate the difference between the votes received by the two best ranked candidates to determine whether the racebetween the two was tight, which would stimulate strategic behavior; 3. we calculate the second-first ratio (SF-ratio) proposed byGary Cox. Our results show that that only a small percentage of the voters behaved strategically although the newly introducedmixed-member electoral system presents them with the opportunity to do so.